CYBERBULLYING DALAM PERMAINAN INTERAKTIF BERBASIS ONLINE - Halla Sayyidah Muflichah (AKADEMI KOMUNIKASI RADYA BINATAMA, 2022)
The development of technology that is increasingly rapid and advanced to make many changes that occur, including in the form of interactive games. Along with the development of the era, interactive games began to be integrated with technology to emerge online-based video games that are currently very popular with various groups, especially children and adolescents. It is undeniable that interactive games have goals that should have a positive impact on their users. When interactive games are touched by groups who do not understand the game's literacy, the negative impact will be more felt by the player than the positive impact. Online interactive games like Mobile Legends as an example of a game that can have a negative impact on its users. The negative impact that is quite often experienced by users is cyberbullying. This study aimed to determine the types and forms of cyberbullying that were carried out or received by the game users. By using qualitative research methods and data collection through in-depth interviews. With this research, it is hoped that game literacy can reduce the negative impact of the game.